KONSEP PENDIDIKAN BUDI PEKERTI PERSPEKTIF HAMKA - Muhammad Safari Ariga (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2014)
The concept of character education in Hamka's perspective has the notion of forming a mind based on thoughts and syara', as well as making role models as good examples of character. Its purpose is as accommodation or a means of improving oneself and maintaining character. There are three aspects that need to be seen in the concept of character education from Hamka's perspective: 1) The aspect of morality, having a will in a good and virtuous way. 2) Religious aspects, increasing faith and achieving the mind of the Qur'an. 3) Psychological aspects, able to process and utilize emotions to do good.